Penyuluhan, Deteksi Dini, serta Brief Counselling mengenai Drug Abuse pada Remaja - Donatila Mano S; Alicia Sarijuwita; Yohanes Firmansyah; Alexander Halim Santoso (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Drug abuse in adolescents is a serious problem that requires a holistic approach to addressing it. Community education, early detection, and brief counseling are the three main activities that can help prevent and overcome drug abuse in adolescents. Community outreach activities aim to increase youth's understanding of the dangers and negative consequences associated with drug abuse. Community service activities were carried out at one of the high schools (SMA) in Duri Kosambi which included 178 teenagers. Based on the results of the Drug Abuse Screening Test (DAST) questionnaire, it was found that 166 (93.3%) respondents had a scale of 1-5 points. All participants underwent brief counseling and it was found that there were no teenagers with indications of drug abuse. Overall, community outreach activities, early detection, and brief counseling are a comprehensive approach in preventing and overcoming drug abuse in adolescents. Through this approach, it is hoped that adolescents can gain a better understanding of the dangers of drugs, as well as get the necessary support and assistance to overcome these problems. Collaborative efforts between schools, families and medical personnel are key in achieving positive results in dealing with the challenges of drug abuse in adolescents.personnel are key in achieving positive results in dealing with the challenges of drug abuse in adolescents.